Evaluation of the READSI Program as a Model for Strengthening Village Government Capacity in Islamic Value-Based Entrepreneurial Education for Millennial Farmers Islam - Isran Kadir Passan; Kaharuddin; Baso Hasyim; Dodi Ilham (Institut Pemerintahan Dalam Negeri Kampus Sulawesi Selatan, 2025)
This study aims to evaluate the implementation of the Rural Empowerment and Agricultural Development Scaling Up Initiative (READSI) as a model for strengthening village government capacity in the entrepreneurial education of millennial farmers based on Islamic values in Kalibamamase Village, Luwu Regency. This research uses a qualitative approach with the CIPP evaluation model (Context, Input, Process, Product) to assess the relevance of the program, the readiness of resources, and the effectiveness of village governance in integrating Islamic values into entrepreneurial practices. Data were collected through in- depth interviews, observations, and documentation, then analyzed using the interactive model of Miles and Huberman. The results show that, from the context aspect, the READSI program is relevant to the socio- economic needs of rural communities, particularly in improving financial literacy and the entrepreneurial culture of millennial farmers. In terms of input, the success of the program is influenced by the institutional support of the village government, the competence of facilitators, and community participation, although there are still challenges in adjusting training materials and post-program sustainability strategies. The integration of Islamic values such as ß╣úidq (honesty), am─ünah (responsibility), and ╩┐adl (justice) has proven to strengthen collective ethics and transparency in village business management. This study concludes that the READSI program not only contributes to the economic well-being of farmers but also strengthens public morality, participatory village governance, and justice.